Instability and uncertainty of carbon storage in karst regions under land use change: a case study in Guiyang, China - Zhou, Heng; Tang, Mingdong; Huang, Jun; Zhang, Jinting; Huang, Jingnan; Zhao, Haijuan; Yu, Yize (Frontiers in Environmental Science, 2025)
IntroductionKarst regions are integral to the global carbon cycle. However, land use changes of karst regions driven by urbanization and desertification contribute to the instability of carbon storage, leading to uncertainties in the future. Understanding these instabilities and uncertainties is crucial for formulating carbon sequestration and land management strategies.MethodsThis study employed Patch-generating Land Use Simulation (PLUS) and Integrated Valuation of Ecosystem Services and Trade-offs (InVEST) to estimate carbon storage, and introduced the Coefficient of Variation (CV) to assess the instability and uncertainty. Multiscale Geographically Weighted Regression (MGWR) was applied to explore the mechanisms, while Polynomial Regression (PR) identified the stable intervals of factors, informing land-use policies.Results and Discussion(1) From 2000 to 2020, Guiyang’s carbon storage rose from 136.62 Tg to 142.13 Tg. By 2035, projections under natural development, urban expansion, and ecological protection scenarios estimate increases to 147.50 Tg, 147.40 Tg, and 147.82 Tg, respectively. (2) Carbon storage instability increased from 2000 to 2020, while uncertainty is expected to decrease by 2035. Instability was primarily due to transitions of Cropland-Forest, Forest-Cropland, Cropland-Grassland, and Cropland-Impervious, while uncertainties mainly arise from Cropland-Forest, Cropland-Impervious, and Grassland-Impervious transitions. (3) DEM, AI, Distance from national highways, SHDI, and Mean annual precipitation affected instability significantly. (4) Encouraging Shrub-Forest, Shrub-Cropland and Cropland-Forest conversions, and controlling Forest-Cropland, Forest-Shrub, and Cropland-Impervious conversions within the stable intervals of factors, can enhance carbon storage and reduce uncertainty. This study establishes a methodology for evaluating carbon storage instability and uncertainty in karst regions, which is an extension of carbon storage research.